3D kinematic analysis of the ollie maneuver on the skateboard - Bianchini Wood, L.; Oliveira, A.; Santos, K.; Rodacki, A.; Lara, J. (Apunts Educación Física y Deportes, 2020)
This study aims to analyze the tridimensional kinematics of the ollie maneuver on the skateboard and to compare static and dynamic maneuver performance, i.e., without and with a previous row, respectively. Six male participants were analyzed. Thirty-four reflective markers were placed on the skateboarder`s body and four reflective markers on the board. The tridimensional analysis was captured by eleven cameras (100 Hz) (Vicon® system). The analysis of the ollie skateboard maneuver was performed in two different ways: a) without (static maneuver) and b) with (dynamic maneuver) a previous row. The joint angles (ankle, knee and hip), during maximal height center of mass of participants and the skateboard, were compared using the Student`s T-test. The correlation between the center of mass of the participant and the skateboard was calculated using the Pearson Correlation. No significant differences were observed in the maximum height of the joint angles and centers of mass of the participants and the skateboard. The maximal height of the participant`s and the skateboard`s center of mass did not present a significant correlation. The results showed that there is no difference between performing the ollie skateboard maneuver with (static) or without (dynamic) a previous row. However, training to increase the height and improve the performance of the maneuver in general is essential for the skateboarder to achieve a higher score and a greater likelihood of success in sports competitions.